2011
DOI: 10.4103/0972-0707.82600
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro evaluation of microleakage in class V preparations restored with Hybrid versus Silorane composites

Abstract: Aim:To compare the difference in microleakage values using conventional and new low-shrink Silorane composites using the dye penetration method.Background:With improvement in adhesive technology, problems associated with composites have been largely overcome. However, microleakage due to polymerization shrinkage still remains a challenge. New Silorane-based composites are alleged to have less than 1% polymerization shrinkage, which would potentially decrease the microleakage, and hence, resolve this longstandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…This method has been contested because it is an evaluation of a subjective nature, in which the degree of dye penetration is calculated by means of scores. 19 Therefore, to minimize the inter-examiner subjectivity, in this study, the evaluators underwent a process of calibration and the Kappa index was calculated (K> 82%).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been contested because it is an evaluation of a subjective nature, in which the degree of dye penetration is calculated by means of scores. 19 Therefore, to minimize the inter-examiner subjectivity, in this study, the evaluators underwent a process of calibration and the Kappa index was calculated (K> 82%).…”
Section: Discussionmentioning
confidence: 99%
“…Authors who have found no statistically significant differences in microlekage scores of siloranes and methacrylate composites are Ernst et al and Umer et al (14,15). Both used hybrid composites.…”
Section: Discussionmentioning
confidence: 99%
“…Dye penetration along the occlusal and cervical margins of the tooth-restoration interface was evaluated by two independent observers and recorded as follows: 0 = no dye penetration, 1 = penetration involving half the occlusal/gingival wall, 2 = penetration involving more than half the occlusal/gingival wall, and 3 = penetration involving the axial wall. [11]…”
Section: Methodsmentioning
confidence: 99%